2004
DOI: 10.3171/jns.2004.100.4.0672
|View full text |Cite
|
Sign up to set email alerts
|

Deferoxamine-induced attenuation of brain edema and neurological deficits in a rat model of intracerebral hemorrhage

Abstract: Deferoxamine and other iron chelators may be potential therapeutic agents for ICH. They may act by reducing the oxidative stress caused by the release of iron from the hematoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 267 publications
(118 citation statements)
references
References 36 publications
4
110
0
4
Order By: Relevance
“…Several studies have shown that hemoglobin and its degradation products, in particular iron, resulting from erythrocyte lysis after ICH exert neurotoxic effects and contribute to the development and progression of brain edema following ICH and that treatment with iron chelators can reduce these effects [1,2,3,4, 16, 17]. There have not been many clinical studies examining the status and role of iron in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that hemoglobin and its degradation products, in particular iron, resulting from erythrocyte lysis after ICH exert neurotoxic effects and contribute to the development and progression of brain edema following ICH and that treatment with iron chelators can reduce these effects [1,2,3,4, 16, 17]. There have not been many clinical studies examining the status and role of iron in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Erythrocyte lysis occurs within 24 hours after ICH, peaking at day 1 to 7 (Nakamura et al, 2004; Wu et al, 2003; Xi et al, 2006), and hemoglobin- and iron-mediated brain injuries occur along with lysis of extravasated erythrocytes. Injection of hemoglobin and its degradation products into striatum also cause brain damage (Hua et al, 2003; Huang et al, 2002).…”
Section: Primary and Secondary Brain Injury After Ichmentioning
confidence: 99%
“…(4, 5) In animal models of ICH, PHE is consistently associated with worse neurological outcome. (6) Currently, however, the relationship between PHE and outcome in ICH patients is controversial, since studies examining this question have shown conflicting results. (7, 8) This critical gap in knowledge severely impedes translation of novel therapies for ICH.…”
Section: Introductionmentioning
confidence: 99%